Thermal decomposition and shelf-life of PETN and PBX based on PETN using thermal methods - Toan, Nguyen Trung; Nhan, Phan Duc; Phuong, Vo Hoang (Vietnam Journal of Science and Technology, 2018)
The kinetics of exothermic reactions are important in assessing the potential of materials and systems for thermal explosion. In this paper, the thermal behavior and decomposition kinetics of pentaerythritol tetranitrate (PETN) and polymer-bonded explosives (PBXs) based on PETN were investigated using Thermogravimetric analysis (TGA) and Vacuum Stability Test (VST) methods. The Arrhenius activation energies and pre-exponential factors were determined by the Ozawa and Kissinger methods. Based on the overall kinetic parameters of decomposition reactions, the shelf-life of PETN and PBXs based on PETN could be calculated and predicted